1988
DOI: 10.1677/joe.0.1160155
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian steroids modulate the action of calcitonin in women

Abstract: Slow i.v. infusion of salmon calcitonin into normal women led to a transient increase in plasma concentrations of cyclic AMP and to a decrease in plasma calcium, which was maintained for at least 2 h. These responses were significantly reduced in the same patients after hysterectomy and ovariectomy. In contrast, maintenance of the ovaries at the time of surgery, or substitutive hormonal therapy, seemed to restore the sensitivity to exogenous calcitonin, suggesting a permissive role of ovarian steroids in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A major unanswered question is whether estrogen action on bone in vivo is direct or indirect (4,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). It has been suggested that in vivo estrogen promotes the systemic production of growth factors, so-called estromedins, or the removal of growth inhibitors, estrocolyons, elsewhere in the body (42).…”
Section: Discussionmentioning
confidence: 99%
“…A major unanswered question is whether estrogen action on bone in vivo is direct or indirect (4,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). It has been suggested that in vivo estrogen promotes the systemic production of growth factors, so-called estromedins, or the removal of growth inhibitors, estrocolyons, elsewhere in the body (42).…”
Section: Discussionmentioning
confidence: 99%
“…Calcitonin levels do not appear to decline with age (Body and Heath, 1983;Tiegs et al, 1986). Moreover, in the menopause, calcitonin kinetics to provocation do not appear to be consistently altered (Pansini et al, 1988;Stevenson, 1982). It would seem at this point that calcitonin is not an important systemic factor in the development of osteoporosis.…”
Section: Calcitoninmentioning
confidence: 90%